Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
x + 3y = 7 → (1)
2x + 4y = 9 → (2)
Solving for y in the second equation.
Rearrange (1) expressing x in terms of y by subtracting 3y from both sides
x = 7 - 3y → (3)
Substitute x = 7 - 3y into (2)
2(7 - 3y) + 4y = 9 ← distribute and simplify left side
14 - 6y + 4y = 9
14 - 2y = 9 ( subtract 14 from both sides )
- 2y = - 5 ( divide both sides by - 2 )
y = [tex]\frac{5}{2}[/tex]
Substitute this value into (3) for corresponding value of x
x = 7 - 3([tex]\frac{5}{2}[/tex] ) = 7 - [tex]\frac{15}{2}[/tex] = - [tex]\frac{1}{2}[/tex]
Solution is ( - [tex]\frac{1}{2}[/tex], [tex]\frac{5}{2}[/tex] )